Conference Management System / Nik Noraini Nik Farid - Nik Noraini, Nik Farid (2002)
Conference Management System(CMS) is a system that will help on organise and manage a conference for any organisation or company and also to work as a guide for the conference management committee members. This system may be very useful for any organisation who wants to start planning on a conference before, during and after the event. CMS is a web-based system and need a user to key in any information that require and may choose some of the elements that will have link to some websites in order to get some ideas on some of the requirement needed. CMS includes 6 important modules ; Pre-Conference, Accommodation, Transportation, On-site Logistics, Event Management and Post Program. This report is a documentation of presenting my . system in order to help and further up user understanding on the system. Hopefully this system will be the most useful system and maybe very good for the first timer of any organisation who intends to plan on helding a conference and also could replace some of the paper works.